Amethyst Deposits of the Los Catalanes Gemological District (Artigas Department): The First Uruguayan IUGS Geological Heritage Site - César Goso; Mauricio Faraone (Geoconservation Research)
The recognition and valorization of geological heritage in Uruguay is an incipient and developing process. The International Union of Geological Sciences designated the deposits of amethysts of Los Catalanes Gemological District, in northern Uruguay, as one of the first 100 “Geological Heritage Sites” on October 22, 2022, in the Mineralogy category, the first in Uruguay. It is part of one of the most important continental flood volcanism episodes on Earth (end of Jurassic to Early Cretaceous). The Paraná igneous province, a dominant tholeiitic basaltic and scarce acidic province that extends into parts of Brazil, Paraguay, Argentina and Uruguay, contains amethyst and agate deposits of unique international significance because of frequent mega-geode concentration, enormous reserves, and gemstone quality of varied size and forms. Although quartz-filled geodic cavities are common in the southern Serra Geral Formation in Brazil (Ametista do Sul, Quaraí), the more intense purple amethysts in giant geode deposits are found in the Arapey Formation in the lower-middle basin of the Catalán Grande stream in Uruguay. This contributes to the empowerment and pride of the local population as well as raising awareness of the need for the conservation of part of this mineral resource. Further, there was a recent inventory assessment that contributed to the understanding of the real scientific value of this designation.